The Influence of Educational Level and Financial Knowledge on Investment Decisions Mediated by Financial Literacy in Generation Z and Millennials - Nurul Anissa; Osly Usman (Journal of Digital Business and Global Economy, 2026)
The study attempts to explore the factors affecting investment decisions amongst Generation Z and Millennials in the fast-evolving digital financial environment. Particularly, the study aims at determining the effects of education levels and financial knowledge on investment decision-making processes as well as the possibility of financial literacy acting as a mediator. An explanatory quantitative research design was employed in this investigation in order to collect information from a target group of young people who invested their funds using Structural Equation Modeling in SmartPLS. The findings demonstrate that education level does not have any effect on investment decision-making but it enhances financial literacy. In addition, although financial knowledge has a significant effect on making investment decisions, it is not associated with financial literacy. Importantly, the results indicate that financial literacy is the strongest predictor of investments as well as the best full mediator of the education-investment relationship. This finding provides a practical perspective for financial organizations as well as designers of digital platforms aiming at enhancing youth market penetration by constructing a proper educational structure instead of just imparting information.